Smartphone-based Indoor Positioning Using Wi-Fi Fine Timing Measurement Protocol - Huilla, Sami (My University, 2019)
Location-based services have grown popular since GPS and other satellite navigation systems became available for consumers. However, because satellite signals are absent inside buildings, other means of positioning need to be used to enable similar services as outdoors. In the case of mobile phones, Wi-Fi received signal strength has been a widely studied option for positioning. Indoor environment is challenging, because the readings have significant fluctuation due to interference from walls, furniture and people. Fine Timing Measurement (FTM) is a new addition to the IEEE 802.11 WLAN standard. It provides Wi-Fi positioning that relies on the time of flight of the signal instead of its received strength. Time of flight information is supposed to be more reliable compared to signal strength, providing more accurate distance estimates to be used in positioning. FTM is claimed to provide meter-level positioning accuracy. In this thesis, the FTM protocol is introduced, and a smartphone positioning system is implemented. The system includes two alternative Android applications for recording and visualizing FTM data, and two algorithms for calculating position estimates. With an FTM-enabled smartphone and Wi-Fi access points, the positioning accuracy of FTM is evaluated with field measurements in two different office environments. Using an Unscented Kalman Filter algorithm, mean positioning error of 0.72 meters was achieved in a large, open room. In a more scattered AP constellation across multiple rooms, the mean error was 2.07 meters. The results show that meter-level positioning accuracy is possible with FTM, although here it was achieved with favourable AP placements around a single room. In the more realistic setting, room-level accuracy was achieved.

Sijaintitietoon perustuvat palvelut ovat yleistyneet GPS:n ja muiden satelliittipaikannusjärjestelmien tultua kuluttajien käyttöön. Koska satelliittien signaalit eivät kantaudu rakennusten sisälle, vaihtoehtoiset paikannuskeinot ovat tarpeen samanlaisten palveluiden mahdollistamiseksi kuin ulkotiloissa. Älypuhelimien tapauksessa Wi-Fi -signaalinvoimakkuus on paljon tutkittu paikannuskeino. Sisätilat ovat haasteellisia, koska seinät, kalusteet ja ihmiset aiheuttavat merkittävää vaihtelua vastaanotetussa signaalinvoimakkuudessa. Fine Timing Measurement (FTM) on uusi lisäys IEEE 802.11 WLAN -standardiin. Se mahdollistaa Wi-Fi -paikannuksen, joka perustuu signaalin vastaanotetun voimakkuuden sijasta sen lentoaikaan. Lentoaikatiedon oletetaan olevan signaalinvoimakkuutta luotettavampi ja tarkempi keino etäisyyksien arviointiin. FTM:n väitetään mahdollistavan metritason paikannustarkkuuden. Tässä tutkielmassa käsitellään FTM-protokollan toiminta ja toteutetaan sitä hyödyntävä älypuhelimen paikannusjärjestelmä. Toteutus sisältää kaksi vaihtoehtoista Android-sovellusta FTM-datan keruuseen ja visualisointiin sekä kaksi algoritmia sijaintiarvioiden laskemiseen. FTM:n paikannustarkkuutta arvioidaan suorittamalla koemittauksia kahdessa erilaisessa toimistoympäristössä käyttäen protokollaa tukevaa älypuhelinta ja Wi-Fi -tukiasemia. Unscented Kalman Filter -algoritmilla paikannusvirheen keskiarvoksi saatiin 0,72 metriä isossa, avoimessa huoneessa. Asettelemalla tukiasemat harvemmin useaan huoneeseen keskivirheeksi saatiin 2,07 metriä. Tulosten mukaan metritason paikannustarkkuus on mahdollista FTM:n avulla, joskin tässä tapauksessa se saavutettiin suotuisalla tukiasemien sijoittelulla yhden huoneen ympärille. Todenmukaisemmalla sijoittelulla saavutettiin huonetason paikannustarkkuus.
Keywords: Indoor positioning, Fine Timing Measurement, WLAN, UKF, Android